Enantioselective supramolecular devices in the gas phase. Resorcin[4]arene as a model system - Fraschetti, Caterina; Letzel, Matthias C.; Filippi, Antonello; Speranza, Maurizio; Mattay, Jochen (Beilstein Journal of Organic Chemistry, 2012)
This review describes the state-of-art in the field of the gas-phase reactivity of diastereomeric complexes formed between a chiral artificial receptor and a biologically active molecule. The presented experimental approach is a ligand-displacement reaction carried out in a nano ESI-FT-ICR instrument, supported by a thermodynamic MS-study and molecular-mechanics and molecular-dynamics (MM/MD) computational techniques. The noncovalent ion–molecule complexes are ideal for the study of chiral recognition in the absence of complicating solvent and counterion effects.
Keywords: diastereomeric complexes; gas phase enantioselectivity; kinetics; mass spectrometry; resorcin[4]arene receptor